VD_FINDINFO Jug / 2024 / 275 vom 15. November 2023 - VD Tribunal cantonal (2023)
BRIGANDAGE, PARTIE CIVILE, FIXATION DE LA PEINE, CONSTATATION DES FAITS | 140 ch. 1 CP, 47 CP, 49 al. 1 CP, 10 CPP (CH), 126 CPP (CH)